2013
DOI: 10.1021/ja3101215
|View full text |Cite
|
Sign up to set email alerts
|

DNA-Mediated Assembly of Protein Heterodimers on Membrane Surfaces

Abstract: We present a method based on self-assembling oligonucleotides to anchor proteins to a supported membrane surface. This anchoring method allows control of the surface density of multiple proteins. By incorporating additional recognition sequences into the DNA linkers, defined heterodimers can be produced upon the addition of a heterospecific DNA cross-linking strand. Characterization by fluorescence cross-correlation spectroscopy (FCCS) confirmed lateral mobility and the formation of specific heterodimers. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 61 publications
1
32
0
Order By: Relevance
“…In contrast, oligonucleotide base-pairing interactions are well understood, form with high fidelity, and have been widely used as a means for assembling diverse supramolecular shapes that can act as scaffolds for organizing the assembly of external molecules, including proteins or protein-based virus capsids (35)(36)(37)(38)(39)(40). By replacing the formation of protein-protein interactions with oligonucleotide hybridization, we have shown that crystalline superlattices can be assembled from a single protein, multiple proteins, or a combination of proteins and AuNPs.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, oligonucleotide base-pairing interactions are well understood, form with high fidelity, and have been widely used as a means for assembling diverse supramolecular shapes that can act as scaffolds for organizing the assembly of external molecules, including proteins or protein-based virus capsids (35)(36)(37)(38)(39)(40). By replacing the formation of protein-protein interactions with oligonucleotide hybridization, we have shown that crystalline superlattices can be assembled from a single protein, multiple proteins, or a combination of proteins and AuNPs.…”
Section: Discussionmentioning
confidence: 99%
“…Despite notable recent achievements (32,33), the de novo design of protein-protein interactions, especially to form supramolecular structures beyond dimeric complexes, remains difficult due to a lack of universal interaction motifs (34). In contrast, oligonucleotide base-pairing interactions are well understood, form with high fidelity, and have been widely used as a means for assembling diverse supramolecular shapes that can act as scaffolds for organizing the assembly of external molecules, including proteins or protein-based virus capsids (35)(36)(37)(38)(39)(40). By replacing the formation of protein-protein interactions with oligonucleotide hybridization, we have shown that crystalline superlattices can be assembled from a single protein, multiple proteins, or a combination of proteins and AuNPs.…”
Section: Discussionmentioning
confidence: 99%
“…They then constructed a paracrine signaling network in these isolated artificial 3D microtissues. In addition to patterning cells, another study reported by Coyle et al [133] has shown that a DNAbased strategy can also be used to mediate the assembly of proteins into defined heterodimers or higher-order oligomers on supported membranes, which can then be used to direct the molecular composition of cell membrane receptor clusters. Moreover, instead of using simple ssDNA strands, Langecker et al [134] used scaffolded DNA origami to create lipid membrane channels composed of a stem that penetrated and spanned a lipid membrane, as well as a barrel-shaped cap that adhered to the membrane ( Figure 6E).…”
Section: Surface Engineering Of Live Cell With Dna Nanostructuresmentioning
confidence: 99%